The Potential Protective Role Of Vitamins C Against Adverse Effects Of Some Plant Growth Regulators In Albino Rats (Journal of Pharmaceutical Negative Results, 2023)
Gibberellic acid (GA3) and Ethephon (ETP) are plant growth regulators that are largely used in agriculture to accelerate and control the production of many vegetables and fruits. This study aimed to evaluate the toxicity of GA3 and ETP and protective role of vitamin C on some immunological, hematological and liver function parameters in albino rats. Animals were divided into six groups (6 animals per group) as follows: G1, the control group, received saline solution (1ml/kg). G2 received vitamin C (200 mg/kg). G3 received GA3 (75 mg/kg). G4 was given ETP (150 mg/kg). G5 received vitamin C+GA3 with the same previous doses. G6 was given vitamin C+ETP with the same previous doses. All doses were given orally and once daily for six weeks. The results showed significant decrease in levels of total immunoglobulins (Igs), IgG, IgA, and IgM and increase in serum pro-inflammatory cytokines INF-γ, TNF-α, IL-1β and IL-6 compared with control group. Significant increase in total WBCs and lymphocytes and decrease in neutrophils were recorded, in addition to, significant decrease in RBCs and hemoglobin content compared with control group. Moreover, elevated levels of ALT, AST, ALP, GGT, bilirubin and AFP and decreased levels of total proteins and albumins were indicated in GA3 and ETP groups. Liver lipid peroxidation (MDA) and nitric oxide (NO) levels were significantly elevated and liver antioxidant enzymes SOD and CAT and GSH content were significantly decreased in GA3 and ETP groups. Administration of vitamin C with GA3 and ETP ameliorated most of the previous changes caused by GA3 and ETP administration. It could be concluded that both GA3 and ETP could induce alterations in liver functions, immunological, hematological and oxidative stress parameters in rats and vitamin C could ameliorate these changes because of its anti-inflammatory, antioxidant and free radicals scavenging properties.